Features of using immersive technologies (virtual and augumented reality) in medical education and practice - Kovalchuk, O. I.; Bondarenko, M. P.; Okhrey, A. G.; Prybytko, I. Y.; Reshetnyk, E. M. (Морфологія / Morphologia / Morfologìâ, 2020)
Nowadays, the subject of research is to study the characteristics of the impact of the usage of immersive technologies on the quality of the educational process. Using the equipment of the virtual reality rooms of the Educational and Research Center "Institute of Biology and Medicine" of Taras Shevchenko National University of Kyiv to implement immersive technologies in the modern educational process, students are approaching the peaks of professionalism in the future. Learning with the use of immersive technologies contributes to the formation of focus on the practical component of education, increase the productivity of the educational process, increase attention, adapt the speed of information retrieval, increase motivation, improve creativity and memory, allow comprehensive assessment of educational achievements. contributes to the provision of quality, modern, visual and optimized training of medical personnel.